The application and adaption of the organizational capacity framework on sports clubs to identify causes for organizational problems - Carina Post (Europäisches Institut für Sozioökonomie e.V., 2021)
Scientific reflections of sports clubs are confronted with the problem of finding an appropriate approach to reflect the diversity of sports-related organizations. The purpose of this study is to observe the performance of sports clubs by considering the problems that occur. In order to capture the organizations in a model, the organizational capacity framework is presented. Since previous scientific studies have not resulted in standardized variables, a specific selection of relevant aspects is required. The framework captures the interdependent influence of human, financial, process and infrastructural, network and relationship as well as planning and development resources within the organization. The potential usefulness of the application of the framework is tested on sports clubs in the Rhineland (n = 1,000). The results of the multiple regression show that the organizational capacity framework is suitable to be applied on sports clubs, but requires further research to obtain more meaningful statements. Regarding organizational problems, it is indicated that board members, sufficient finances, strategic planning, and availability and accessibility of facilities are most important to reduce problems. Practical implications are addressed to both sports clubs and umbrella organizations. – – Die wissenschaftliche Betrachtung von Sportvereinen steht vor dem Problem, einen geeigneten Ansatz zu finden, der die Vielfalt der sportbezogenen Organisationen abbildet. Das Ziel dieser Studie ist es, die Leistung von Sportvereinen unter Berücksichtigung der auftretenden Probleme zu beobachten. Um die Organisationen in einem Modell zu berücksichtigen, wird der Ansatz Organizational Capacity vorgestellt. Da die bisherigen wissenschaftlichen Untersuchungen nicht zu standardisierten Variablen geführt haben, muss jeweils eine spezifische Auswahl der relevanten Aspekte vorgenommen werden. Organizational Capacity erfasst den gegenseitigen Einfluss von Human-, Finanz-, Prozess- und Infrastruktur-, Netzwerk- und Beziehungsressourcen sowie Planungs- und Entwicklungsressourcen innerhalb der Organisation. Der praktische Nutzen wird an Sportvereinen im Rheinland (n = 1.000) getestet. Die Ergebnisse der multiplen Regression zeigen, dass die Heuristik für die Anwendung auf Sportvereine geeignet ist, aber weitere Forschung erfordert, um aussagekräftigere Aussagen zu erhalten. In Bezug auf organisatorische Probleme wird angegeben, dass Vorstandsmitglieder, ausreichende finanzielle Mittel, strategische Planung sowie die Verfügbarkeit und Zugänglichkeit von Sportanlagen am wichtigsten sind, um Probleme in Sportvereinen zu verringern. Praktische Implikationen richten sich sowohl an Sportvereine als auch an den Verband.
urn:nbn:de:bsz:291–ds-346466; hdl:20.500.11880/31724
Keywords: 300; Organizational Capacity; Resources; Sports Clubs; Organizational Problems; Performance; Ressourcen; Sportvereine; Organisatorische Probleme